Geotechnical measures for stabilization of the Aqueduct in Skopje - Jovan Br. Papić, Igor Peševski, Atanas Strašeski, Radica Jovanova (My University, 2022)
One of the last remaining aqueducts on the Balkan Peninsula is located in Skopje, the capital of R. N. Macedonia. It is about 400 m long and 6 m high. Unfortunately, it has suffered destruction both from geotechnical, earthquake and vandalism reasons, while recently two inclinations have appeared: both are about 50 cm in size and at lengths of approximately 25 m. In order to determine the reasons for such damages, both historical and existing technical documents were reviewed, since some activities were realized several years ago. However, additional geotechnical investigations and tests were performed. It was found that there are very heterogeneous soil conditions beneath and along the structure, including soils with high swelling capacity. In addition, the location itself is swampy and is a seismic prone area where, moreover, two faults were detected nearby. Thus, the project had to deal with all these elements and to supply permanent stabilization. Several different techniques were analyzed and compared from technical and economical aspect. The paper digests the performed field and laboratory tests, the numerical analyses modelling, the difficult conditions and the behaviour of the aqueduct, and presents the geotechnical measures to restore it.
Keywords: aqueduct, inclination, stabilization, swelling, micropiles.